Yogurt and curd cheese as alternative ingredients to improve the gluten-free breadmaking - Graça, Carla; Raymundo, Anabela; Sousa, Isabel (Frontiers in Nutrition, 2022)
Gluten-free products are on today´s agenda since they represent the most hastily growing segments in the market, representing an opportunity for food companies. Nevertheless, it is well-known that gluten is a crucial network structure in wheat dough systems, which accounts for the overall desired technological features of the final bakery goods. Therefore, the absence of gluten negatively affects the characteristics of gluten-free bread, triggering a technological challenge in the manufacturing of products with resembled characteristics of wheat derived-counterparts. The search for new protein sources has been studied as an approach to circumvent the technological drawbacks of gluten removal. Dairy proteins are functional molecules that can likely be capable of building up a protein-network structure so that it would improve the technological properties of gluten-free products. In the present work, different levels of dairy products addition (10 % and 20 %, w/w) were used to supplement the gluten-free bread formulas, and the impact on dough rheology properties was well correlated to the bread technological quality parameters obtained. Linear correlations (R2> 0.904) between steady shear (viscosity) and oscillatory (elastic and viscous moduli) values of the dough rheology with bread quality parameters (volume and firmness), were obtained, suggesting that the bread quality improvements are proportional to the levels of dairies added. Likewise, strong linear correlations (R2 > - 0.910) between pasting properties parameters and bread staling rate, supported the hypothesis that the dairies tested have a high potential to generate bread with a lower staling rate, which is an advantage to extending the shelf-life. In short, results confirmed that the addition of both dairy products, as bakery ingredients, can constitute a technological advantage to improve the overall gluten-free bread quality.